Праисторијско налазиште Ђула у Остриковцу код Светозарева - Stojić, Milorad (Balcanica - Annual of the Institute for Balkan Studies, 1989)
On the location of Đula in Ostrikovac completely, and on 24 other locations in the region of Morava river in part, the period of Eneolithic was documented which corresponds to its development in the entire region of Danube river from the end of Baden phase to the late period of Vučedol cultural group. On the basis of stratification in Ostrikovac and greater number of single layer settlements, four phases of development of that long eneolithic cultural manifestation were ackowledged (Ostrikovac 1-a — 1-d). However, it was not defined as a separate cultural group because of the lack of certain important data, like those about its spreading, economy, accomodations, burials and religion. Vinkovac closed entities in Ostrikovac enabled the periodization of that particular cultural group in the Morava river region. Due to the ceramics from Vatin which was found in a ceratin number of Vinkovac pits in Ostrikovac, important data were received, relevant for the relative chronology of two cultural groups of the bronze age, Vinkovac and Vatin. The explorations in Ostrikovac opened numeruos new questions, like the cultural and chronological interpretation of ceramic findings belonging to the culture of bell cups in Djula and other locations in the Morava river region, or the question of relative chronology and cultural relations between Vinkovac and Bubanj—Hum III group in the region of Morava river. By all means, future reserch in Ostrikovac and other locations should give answers to some of those questions and thus contribute to better knowledge of the metal age in the Morava river region.